Multi-component mixture of dipolar hard spheres with surface adhesion - Protsykevich, I.A. (Condensed Matter Physics, 2003)
Solution of the mean spherical approximation for multi-component model of dipolar hard spheres with surface adhesion is obtained using factorization technique pioneered by Wertheim and Baxter. For the sake of illustration numerical calculations for the dielectric constant of the two-component version of the model are carried out.